EDUCATION: REAL AND DUE ОБРАЗОВАНИЕ: СУЩЕЕ И ДОЛЖНОЕ ОСВІТА: СУЩЕ ТА НАЛЕЖНЕ - V. V. Khmel (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
The current context of information society is characterized by the growing role and importance of educational technology. To the fore the question of what should be a process of education
in the postmodern situation and on the basis of the Bologna concept. The article contains a comparative analysis of educational systems of Germany, Russia and Ukraine. Нынешний контекст информатизации общества характеризуется возрастанием роли и значимости образовательных технологий. На первый план выходит вопрос о том, каким должен быть процесс образования в ситуации постмодерна и на базе Болонской концепции. Статья содержит сравнительный анализ систем образования Германии, Росси и Украины. В нинішньому контексті інформатизації суспільства зростає роль та значимість освітніх технологій. В центрі уваги знаходиться проблема належного вигляду процесу освіти в ситуації постмодерну та на основі Болонської концепції. Стаття містить порівняльний аналіз систем освіти в Германії, Росії та Україні.